0
$\begingroup$

Stalling says:

OFB encryption can be expressed as

Cj = Pj⊕E(K, Oj-1)

where

Oj-1 = E(K, Oj-2)

Some thought should convince you that we can rewrite the encryption expression as:

Cj = Pj⊕E(K, [Cj-1 ⊕Pj-1])

Is he implicitly saying that

[Cj-1 ⊕Pj-1] = Oj-1

? If yes, why?

$\endgroup$
1
$\begingroup$

Is he implicitly saying that

[Cj-1 ⊕Pj-1] = Oj-1

Yes, this is true.

? If yes, why?

Well, we know that:

$$C_{j-1} = P_{j-1} \oplus E(K, O_{j-2})$$

(this is the first formula, replacing $j$ with $j-1$), and we know that:

$$O_{j-1} = E(K, O_{j-2})$$

Combining the two, we get:

$$C_{j-1} = P_{j-1} \oplus O_{j-1}$$

or, in other words:

$$C_{j-1} \oplus P_{j-1} = O_{j-1}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.